Immunohistochemical Changes of Polycystic Ovaries in rats Treated with Asparagus Officinalis L. Roots Extract - Farah Jawad Al-masoudi; Ashwaq Kadhem Obeid (Medical Journal of Babylon)
Background:Polycystic ovary syndrome (PCOS) which a series reproductive, metabolic and psychological condition that is characterized by abnormal gonadotropin secretion or hyperandrogenism and associated with insulin resistance and most commonly found in the reproductive age female. Objectives:This research paper were conducted to examine the effects of Asparagus officinalis L. roots extract on letrozole induced PCOS where the effect of 400 mg/kg A. officinalis L. root extract on the PCOS was studied for 28 days in female rats. Materials and Methods:Thirty-five female Albino rats were randomly divided into five groups, including control negative group, positive control, PCOS, treatment and preventive group. During 28 days, the positive control group got an extract of the A. officinalis roots. Letrozole 1 mg/kg dissolve in 0.5% carboxymethyl cellulose solution was used to cause PCOS for 28 days. Following the induction of PCOS, the treatment group received extract A. officinalis roots for 28 days. The preventative group received an extract of asparagus roots during PCOS induction. Results:Immunohistochemical results are shown Ovary slices from of the therapeutic and preventative groups next to the asparagus group were immunostained for Ki 67, which showed high positive statistically (P <0.05) immunological activity in the granulosa nuclei and less in the theca cells. When compared to the PCOS group, both the granulosa and theca layers had very weak positive immunostaining (P <0.05). According to the morphological findings, granulosa cells from the Control group and asparagus group proliferated much more than granulosa cells from the PCOS group statistically significant (P <0.05). Conclusion:The findings show that theca and granulosa cells are quickly stimulated to proliferate by asparagus root extract. Moreover, it therefore speeds up oogenesis and early cell divisions.